Skills supply and demand in Europe : medium-term forecast up to 2020 - (:unkn) unknown (Publications Office of the European Union, 2010)
Anticipation of changing skill needs lies at the heart of the new skill for new jobs agenda. The new Cedefop forecast of changing skill demand and supply in Europe (EU-27, Norway and Switzerland) up to 2020 updates the forecasts carried out in 2007-08 by applying improved data and methods. It also attempts to estimate the medium-term impact of the financial crisis of 2008, and the subsequent recession, based on the available data. The forecast suggests that aggregate demand and supply trends across countries are converging in the medium to longer term, but we need to dig deeper to grasp what is really going on. Changing skill needs, job polarisation and skill mismatch interact in complex ways. The forecasts in this report shed some light on these phenomena, but better data are urgently needed for more analysis. (BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; T 1.5 International vergleichende Berufsbildungsforschung; I 2.2 Europa; Qualifikationsbedarf; Früherkennung; Beschäftigungsentwicklung; Wirtschaftszweig; Bildungsabschluss; Wirtschaftskrise; Prognose; Szenario; Europäische Union; Norwegen; Schweiz; Quantitative Angaben; 2000-2020; 2010-2020